Impaired platelet nitric oxide response in patients with new onset atrial fibrillation. (20th January 2015) - Procter, Nathan E.K.; Ball, Jocasta; Liu, Saifei; Hurst, Nicola; Nooney, Vivek B.; Goh, Vincent; Stafford, Irene; Heresztyn, Tamila; Carrington, Melinda; Ngo, Doan T.M.; Hylek, Elaine M.; Isenberg, Jeffrey S.; et al.
Abstract: Background: Clinical factors associated with thromboembolic risk in AF patients are well characterized and include new onset AF. Biochemically, AF is associated with inflammatory activation and impairment of nitric oxide (NO) signalling, which may also predispose to thromboembolism: the bases for variability in these anomalies have not been identified. We therefore sought to identify correlates of impaired platelet NO signalling in patients hospitalized with atrial fibrillation (AF), and to evaluate the impact of acuity of AF. Methods: 87 patients hospitalized with AF were evaluated. Platelet aggregation, and its inhibition by the NO donor sodium nitroprusside, was evaluated using whole blood impedance aggregometry. Correlates of impaired NO response were examined and repeated in a "validation" cohort of acute cardiac illnesses. Results: Whilst clinical risk scores were not significantly correlated with integrity of NO signalling, new onset AF was associated with impaired NO response (6 ± 5% inhibition versus 25 ± 4% inhibition for chronic AF, p < 0.01). New onset AF was a multivariate correlate (p < 0.01) of impaired NO signalling, along with platelet ADP response (p < 0.001), whereas the associated tachycardia was not. Platelet ADP response was predicted by elevation of plasma thrombospondin-1 concentrations (p < 0.01). Validation cohort evaluations confirmed that acute AF was associated with significant (p < 0.05) impairment of platelet NO response, and that neither acute heart failure nor acute coronary syndromes were associated with similar impairment. Conclusion: Recent onset of AF is associated with marked impairment of platelet NO response. These findings may contribute to thromboembolic risk in such patients. Highlights: New Onset AF is associated with impaired platelet NO response. This impairment is independent of tachycardia. Multivariate determinants of platelet NO response were: new onset AF; statins; platelet aggregability; plasma creatinine. Determinants of platelet aggregability were female sex, admission heart rate, plasma TSP-1 and plasma SDMA.